(untitled) (Research, Society and Development, 2022)
Introduction: Technologies are part of the contemporary world and act as a resource for carrying out various everyday activities. In this way, initiatives for the digital inclusion of the older adults are potentially favorable spaces for the instrumentalization of this population in the use of technological information and communication devices. Objective: Analyze the perceptions of the older adults about barriers and facilitators in the digital inclusion process. Materials and Methods: Qualitative research carried out with 56 older adults people aged between 60 and 83 years. Data collection was carried out through a focus group and reflective field diaries. Data were examined using Bardin’s content analysis. Results: The barriers that appeared in this study are related to the person, their social environment and technology itself. Regarding the facilitators, aspects related to the sense of self-efficacy, interest and perception of usefulness were listed, as well as adequate family support, intergenerational solidarity and the teaching and learning methodology. Conclusion: The barriers found in this study were associated by the participants with previous or inadequate experiences of digital inclusion. The facilitators, in turn, were linked to a process that was attentive and adequate to the specificities of acquiring digital skills for the older adults public. Social support appeared as a significant factor, as it presented itself in an ambivalent way, showing the importance of the existence of digital inclusion services for the elderly population, as well as the relevance of the quality of relational and support networks.